Comparative evaluation of the stability of two different dental implant designs and surgical protocols-a pilot study - David E. Simmons; Pooja Maney; Austin G. Teitelbaum; Susan Billiot; Lomesh J. Popat; A. Archontia Palaiologou (SpringerOpen, 2017)
Abstract Background The purpose of this study was to compare a parallel wall design implant to a tapered apex design implant when placed in the posterior maxilla using two different surgical protocols. Methods Twenty-seven patients (30 implants) were divided into three groups. All implants were 4 mm wide in diameter and 8 mm long. Group A received 10 tapered implants (OSPTX) (Astra Tech OsseoSpeed TX™) using the soft bone surgical protocol (TXSoft). Group B received 10 tapered implants (OSPTX) (AstraTech OsseoSpeedTX™) using the standard surgical protocol (TXStd). Group C received 10 parallel wall implants (OSP) (AstraTech OsseoSpeed™) using the standard surgical protocol (OStd). All implants were placed in the posterior maxilla in areas with a minimum of 8-mm crestal bone height. Resonance frequency measurements (implant stability quotient (ISQ)) and torque values were recorded to determine initial implant stability. All implants were uncovered 6 weeks after placement and restored with a functionally loaded resin provisional screw-retained crown. Resonance frequency measurements were recorded at the time of implant placement, at 6 weeks and 6 and 12 months. Twelve months after implant placement, the stability of the implants was recorded and the final restorations were placed using custom CAD/CAM fabricated abutments and cement-retained PFM DSIGN porcelain crowns. After implant restoration, bone levels were measured at 6 and 12 months with standardized radiographs. Results Radiographic mean bone loss was less than 0.5 mm in all groups, with no statistically significant differences between the groups. Implant survival rate at 1 year was 93.3%, with 2/30 implants failing to integrate prior to functional loading at 6 weeks. No statistically significant difference was found between ISQ measurements between the three groups at all time intervals measured. Strong positive correlations were found between overall bone loss at 6 months and insertion torque at time of placement. A very weak correlation was found between insertion torque and ISQ values at time of implant placement. Conclusions Survival and stability of OSPTX and OSP implants is comparable. Osteotomy preparation by either standard or soft bone surgical protocol presented no significant effect on implant survival and stability for the specific implant designs.